Correlational patterns of neuronal activation and epigenetic marks in the basolateral amygdala and piriform cortex following olfactory threat conditioning and extinction in rats - Qin, Tian; Xia, Yue; Nazari, Negar; Sepahvand, Tayebeh; Yuan, Qi (Frontiers in Molecular Neuroscience, 2024)
Introduction Cumulative evidence suggests that sensory cortices interact with the basolateral amygdala (BLA) defense circuitry to mediate threat conditioning, memory retrieval, and extinction learning. The olfactory piriform cortex (PC) has been posited as a critical site for olfactory associative memory. Recently, we have shown that N-methyl-D-aspartate receptor (NMDAR)-dependent plasticity in the PC critically underpins olfactory threat extinction. Aging-associated impairment of olfactory threat extinction is related to the hypofunction of NMDARs in the PC. Methods In this study, we investigated activation of neuronal cFos and epigenetic marks in the BLA and PC using immunohistochemistry, following olfactory threat conditioning and extinction learning in rats. Results We found highly correlated cFos activation between the posterior PC (pPC) and BLA. cFos was correlated with the degree of behavioral freezing in the pPC in both adult and aged rats, and in the BLA only in adult rats. Markers of DNA methylation 5 mC and histone acetylation H3K9/K14ac, H3K27ac, and H4ac exhibited distinct training-, region-, and age-dependent patterns of activation. Strong correlations of epigenetic marks between the BLA and pPC in adult rats were found to be a general feature. Conversely, aged rats only exhibited correlations of H3 acetylations between the two structures. Histone acetylation varied as a function of aging, revealed by a reduction of H3K9/K14ac and an increase of H4ac in aged brains at basal condition and following threat conditioning. Discussion These findings underscore the coordinated role of PC and BLA in olfactory associative memory storage and extinction, with implications for understanding aging related cognitive decline.